Targeted cash assistance as a reformative alternative to the universal in-kind subsidy in Algeria - Lahcene, Fodil; Adila, Khanoussa (International journal of economic perspectives, 2025)
This paper highlights the importance of replacing the Universal In-Kind Subsidy with Targeted Cash Assistance. It is structured into four sections: first, an overview of government subsidy concepts; second, a comparison of Targeted Cash Assistance and Universal In-Kind Subsidies based on various opinions and experiences; third, steps for designing a cash assistance program; and fourth, the reform of the Universal In-Kind Subsidy in Algeria. The findings indicate that Targeted Cash Assistance is more effective, though its successful implementation requires mechanisms to ensure proper targeting, a gradual reduction of in-kind subsidies, and protection for vulnerable groups.